2021
DOI: 10.1017/s1047951121000019
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health conversations in adolescents with CHD

Abstract: Background: Reproductive issues as related to CHD must be discussed in the clinic and at home. Providers can ensure that correct information is imparted to the adolescent and encourage mothers to provide support and guidance to the adolescent. The level to which these conversations occur is unknown. Methods: A survey distributed to female adolescent/mother dyads assessed self-reported conversations with the healthcare provider and between each other about reproductive health topics. A cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Additionally, women with CHD have reported receiving incorrect recommendations regarding contraceptive safety [10][11]. Only about half of women with CHD in prior studies reported receiving information on birth control options and risks from a provider [9][10][11][13][14]. As demonstrated in our study, women frequently expressed concern about a lack of safe contraception options due to CHD.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Additionally, women with CHD have reported receiving incorrect recommendations regarding contraceptive safety [10][11]. Only about half of women with CHD in prior studies reported receiving information on birth control options and risks from a provider [9][10][11][13][14]. As demonstrated in our study, women frequently expressed concern about a lack of safe contraception options due to CHD.…”
Section: Discussionmentioning
confidence: 62%
“…Prior investigations found that one-to two-thirds of women with CHD reported never discussing the risks of pregnancy or the safety of contraception related to their heart condition with a physician [9][10][11][13][14]. Most of the participants in our study report having had a conversation about SRH with a provider at some point; however, many still had misconceptions about their risks and options for care.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations